2020
DOI: 10.1016/j.xplc.2020.100114
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Genotype-by-Environment Interactions to Maintain Genetic Variation in a Model Legume–Rhizobia Mutualism

Abstract: The maintenance of genetic variation in mutualism-related traits is key for understanding mutualism evolution, yet the mechanisms maintaining variation remain unclear. We asked whether genotype-by-environment (G×E) interaction is a potential mechanism maintaining variation in the model legume–rhizobia system, Medicago truncatula–Ensifer meliloti . We planted 50 legume genotypes in a greenhouse under ambient light and shade to reflect reduced carbon availability for plants. We found an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Next we discuss the coevolutionary implications of genotypedependence (G x G interactions), then wrap up with a call for further synthesis with metabolic network models towards systems genetics of symbiosis. (106,88,107,108). Nevertheless we note that these sorts of G × E variants were rare in our study, despite strong rank-order effects among strain means at the organismal level (Table 2); moreover, because our "environments" were simply different greenhouse experiments, relating such antagonistic effects to adaptation in the wild will require the type of in situ studies that are common in plants (e.g., 100, 97, 109) but more difficult in soil microbes.…”
Section: Universal Associations Highlight Transport Functions and Secretion Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next we discuss the coevolutionary implications of genotypedependence (G x G interactions), then wrap up with a call for further synthesis with metabolic network models towards systems genetics of symbiosis. (106,88,107,108). Nevertheless we note that these sorts of G × E variants were rare in our study, despite strong rank-order effects among strain means at the organismal level (Table 2); moreover, because our "environments" were simply different greenhouse experiments, relating such antagonistic effects to adaptation in the wild will require the type of in situ studies that are common in plants (e.g., 100, 97, 109) but more difficult in soil microbes.…”
Section: Universal Associations Highlight Transport Functions and Secretion Systemsmentioning
confidence: 99%
“…Evolutionary change in response to environments implies that the loci underlying selected traits have differential effects on fitness across environments. Here we identify the loci that generate important trait variation both within and among environments, the (90,108,109,110). Nevertheless we note that these sorts of G × E variants were rare in our study, despite strong rank-order effects among strain means at the organismal level (Table 2); moreover, because our "environments" were simply different greenhouse experiments, relating such antagonistic effects to adaptation in the wild will require the type of in situ studies that are common in plants (e.g., 99,102,111) but more difficult in soil microbes.…”
Section: Universal Associations Highlight Transport Functions and Secretion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) assessed the impact of demographic processes on genomic diversity and positive selection in Arabidopsis lyrata by analyzing re-sequencing data from 52 populations collected worldwide. Vaidya and Stinchcombe (2020) used the Medicago truncatula - Ensifer meliloti system to demonstrate that genotype-by-environment interactions make a significant contribution to maintaining genetic variation in mutualisms, and Hodgins et al. (2020) found that invasive populations of Canada thistle show rapid adaptation with no trade-off between stress tolerance and performance.…”
mentioning
confidence: 99%
“…Under this assumption, genotypes that perform well in one environment do poorly in another, ensuring that variation is maintained. Vaidya and Stinchcombe (2020) tested this hypothesis by examining the performance of 50 legume genotypes in different light environments. Changes in genotype fitness rank were observed across light environments, confirming that, as predicted, G × E is responsible for the maintenance of variation in mutualism-enhancing traits in this system.…”
mentioning
confidence: 99%